Strategi Adaptasi UMKM Kuliner dalam Menghadapi Pertumbuhan Ekonomi yang Lemah di Kota Tebing Tinggi - Indra Welly Arifin; Dedy Dwi Arseto (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2025)
This study aims to analyze the adaptation strategies implemented by culinary MSMEs in Tebing Tinggi City in responding to economic pressure. This research employs a qualitative approach with a case study method. Data were collected through in-depth interviews with MSME owners, field observations, and documentation related to operational and marketing activities. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The findings reveal that the adaptation strategies adopted by culinary MSMEs consist of three main categories. First, operational adaptation is carried out through production cost efficiency, adjustment of operating hours, the use of alternative raw materials, and stricter inventory management. Second, product and service innovation is implemented through menu diversification, product simplification, packaging innovation, and improvement of service quality to attract and retain customers. Third, the application of digital marketing is used as a modern adaptation strategy, which includes the utilization of social media, WhatsApp Business, food delivery platforms, and consistent digital branding. These strategies have proven effective in maintaining business stability and sustaining sales turnover amid unstable economic conditions.